Hydropower for green hydrogen production in Turkey - Karayel, G. Kubilay; Javani, Nader; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
The current study develops a hydro-based hydrogen production concept and investigates the utilization of hydroelectric power for green hydrogen production in Turkey. For the hydroelectric power potential calculations, the installed and under construction hydro-electric power plants, run-of-river systems, and reservoir dams are considered for the entire country. The potential capacities of each city are estimated based on the available official and published data by the government agencies, and some reasonable assumptions are also made for detailed analysis and assessment for a feasible hydrogen economy in the country. The results obtained here clearly show that the contribution of hydroelectric energy to hydrogen production is considerable high in promoting countries towards leadership in the field of green hydrogen production. Based on the analysis results, Tur-key's hydro-based green hydrogen production potential is estimated to be 2.26 megatons. S, anliurfa, Elazig ⠁, Diyarbakir, Artvin, and Adana are cities with the highest green hydrogen production potential from hydroelectric power with an annual production capacity of 233.09, 204.92, 175.35, 157.28, and 140.8 kilotons, respectively. The results of this study are expected to help the policymakers to use hydropower energy for planning and developing action plan for the country and help overcome carbon-based fuel usage and its associated pollution. The main idea is to prepare hydrogen maps in detail for each region in Turkey, based on the hydro energy potential by using electrolysers. This, in turn, can be considered in the context of the current policies of the local communities and policymakers to prepare a sustainable energy roadmap for the country.& COPY; 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydro energy; Green hydrogen; Hydroelectric power; Alkaline electrolyser; Renewable energy; Hydrogen production; ENERGY; PLANTS; DAM; Chemistry; Electrochemistry; Energy & Fuels